Proposta de modelo teórico e diretrizes para incubadoras de empresas universitárias orientadas para a sustentabilidade - Gomes, Barbara Maria Fritzen (2023)
Sustainability has been the protagonist of global development, at least until the year 2030, a limit established so that sustainable development based on objectives and goals is following a solid, progressive and prosperous path. Universities are recognized as key agents in achieving sustainability goals and can enhance its operations through the alignment of its intermediate innovation, especially business incubators, to the 2030 Agenda and its objectives, as well as as ESG (environmental, social and governance) principles, seeking to promote business technological technologies that not only observe the premises of a scalable business model and replicable, but that include aspects aimed at promoting socio-environmental impacts and positive economic. Entrepreneurship and sustainable innovation are seen as essential movements for sustainable development. In light of this current scenario, corroborated by the changes caused by the Covid-19 pandemic, the models for business incubators linked to universities need to be rethought, inserting the sustainability and resilience as a backdrop to your actions and assets. The knowledge is still limited in this context, pointing to a need to capture and reflect on the best practices for sustainability-oriented incubators. In this sense, the objective of this study is the development of a theoretical model and guidelines for business incubators sustainability-oriented university-linked businesses (SOBI). The process methodological consists of three stages: exploratory and descriptive, development and validation. The first allowed exploring and describing the current global and Brazilian scenarios of sustainability-oriented incubators. At this stage, research was carried out qualitative with incubators at national and international levels, as well as research international exploratory study, in order to deepen practical knowledge regarding the tonics of sustainability-oriented business incubators. In the next stage, it was carried out the development of the theoretical model and practical guidelines, in order to, in the third stage, carry out validation of these through an assessment of the stakeholders of a business incubator linked to a Brazilian university, allowing the identification of adjustments and revisions necessary to propose a theoretical model suitable for university incubators oriented towards sustainability, as well as a playbook for this direction. You results demonstrate that redirecting business incubators towards sustainability It is an opportunity for universities.